2014
DOI: 10.1007/s12032-014-0866-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of external beam radiotherapy in the treatment of relapsing meningioma

Abstract: The role of radiotherapy in the treatment of relapsing meningiomas is not well established. Data of patients treated with radiotherapy for a relapsing meningioma were retrospectively analyzed. Overall survival (OS) was the primary endpoint of the analysis. Local control and acute and late toxicity rates have been also reported. From April 1986 to February 2011, 37 patients with a diagnosis of recurrent meningioma were treated. Median age was 64 years (range 36-79). A total of 18, 10, 5 and 4 patients were affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…2,7,13,20 However, recent studies assessing volume rather than diameter of residual tumor have demonstrated a significant recurrence in a short time span following radiation therapy. 21 We must insist on the importance of aiming to remove as much of the tumor as possible when complete resection is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,13,20 However, recent studies assessing volume rather than diameter of residual tumor have demonstrated a significant recurrence in a short time span following radiation therapy. 21 We must insist on the importance of aiming to remove as much of the tumor as possible when complete resection is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we deemed that including these patients in our study would result in additional limitations to our meta-analysis. Furthermore, patients with Simpson Grade IV and V excisions were excluded because in such patients recurrence rates were shown to be higher and survival rates lower in previous studies (3,9,13,35). All data gathered from experiments on human subjects were conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Recurrent meningiomas after the first surgery exhibit a more aggressive course than newly diagnosed meningiomas [53]. As several studies show improved salvage control rates with surgery plus RT, or radiation alone versus surgery alone [44,54], the National Comprehensive Cancer Network (NCCN) has advised that recurrent a meningioma should be resected if possible, and an adjuvant RT should be delivered [53].…”
Section: Radiotherapy After Recurrencementioning
confidence: 99%
“…As several studies show improved salvage control rates with surgery plus RT, or radiation alone versus surgery alone [44,54], the National Comprehensive Cancer Network (NCCN) has advised that recurrent a meningioma should be resected if possible, and an adjuvant RT should be delivered [53]. Non-surgical patients should receive RT alone, chemotherapy being reserved for meningioma progressing after RT [55].…”
Section: Radiotherapy After Recurrencementioning
confidence: 99%